A universe of consciousness : how matter becomes imagination - Edelman, Gerald M.; Tononi, Giulio (New York, NY : Basic Books, 2000)
"In A Universe of Consciousness, Edelman and Tononi present an empirically supported full-scale theory of consciousness. The theory provides a scientific understanding of the most general and fundamental properties of consciousness - the private and unitary nature of experience and yet the infinite variety of conscious states, stretching as widely as one's memory and as far as one's imagination." "Edelman and Tononi apply all of the resources and insights of modern neuroscience, from the largest computer models of the brain ever constructed to new experiments that detect the changes in brain activity that actually occur when we are conscious or unconscious of a stimulus. Their arguments build on the radical ideas introduced by Edelman in works that apply Darwinian principles to the development of brain and mind."--BOOK JACKET.
pt. I. The world knot. 1. Consciousness: philosophical paradox or scientific object? ; 2. The special problem of consciousness ; 3. Everyman's private theater: ongoing unity, endless variety -- pt. II. Consciousness and the brain. 4. Building a picture of the brain ; 5. Consciousness and distributed neural activity ; 6. Neural activity integrated and differentiated -- pt. III. Mechanisms of consciousness: the Darwinian perspective. 7. Selectionism ; 8. Nonrepresentational memory ; 9. Perception into memory: the remembered present -- pt. IV. Dealing with plethora: the dynamic core hypothesis. 10. Integration and reenetry ; 11. Consciousness and complexity ; 12. Determining where the knot is tied: the dynamic core hypothesis -- pt. V. Untangling the knot. 13. Qualia and discrimination ; 14. The conscious and the unconscious -- pt. VI. Observer time. 15. Language and the self ; 16. Thinking ; 17. Prisoners of description.
Includes bibliographical references (p. [253]-264) and index.
Keywords: Consciousness -- physiology; Brain -- physiology; Imagination; Mind-Body Relations, Metaphysical; Thinking -- physiology; Consciousness -- Physiological aspects; Brain -- Physiology; Mind and body; Thought and thinking